The persistence of prey-predator model with competition hosts - Majeed, Azhar A.; Raad, Rami (International Journal of Applied Mathematical Research, 2015)
In this paper, the conditions of the occurrence of persistence of a mathematical model consists from four-species Syn- Ecosymbiosis involves a competition hosts for prey are established. Finally, in order to confirm our obtained analytical results, numerical simulations have been done for a hypothetical set of parameter values.